PENGARUH LINGKUNGAN KERJA, SELF-EFFICACY DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN PADA BANK SYARIAH INDONESIA KC LUBUKLINGGAU - Azizah, Latifah Ayu; Batin, Mail Hilian; Lemiyana (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Employee performance is an important factor in supporting the competitiveness of banking companies, including Bank Syariah Indonesia KC Lubuklinggau which continues to strive to improve the quality of human resources. This study aims to analyze the influence of work environment, self-efficacy, and emotional intelligence on employee performance with quantitative methods by distributing questionnaires to all 30 employees using saturated sampling techniques and SPSS data analysis. The results of the study indicate that work environment and self-efficacy have a positive and significant effect on employee performance, while emotional intelligence does not have a significant effect, but simultaneously the three variables have a positive and significant effect on employee performance. The implications of this study emphasize the importance of creating a conducive work environment, increasing employee self-confidence, and managing emotions through coaching and rewards for performance. It is hoped that these efforts can improve employee performance and achieve company goals.